PEMBELAJARAN AKTIF KONSEP “MIKiR” DAN PENGARUHNYA TERHADAP HASIL BELAJAR PESERTA DIDIK - Noviana Noviana; M.Rusdi T; Ahmad Ali (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2021)
MIKiR stands for “Experiencing, Interacting, Communication and Reflecting” which was pioneered by the Tanoto Foundation in collaboration with the government to launch the MIKiR learning program. MIKiR is a learning that encourages activeness in students. The purpose of this study was to see the effect of active learning on the MIKiR concept on the learning outcomes of class XI MIPA students at SMAN 2 Luwu Timur. This research is a quasi-experimental type (Quasi Experimental Research) with Non-Equivalent Control Group Design. The population in this study were all students in class XI which consisted of 6 classes with a total of 214 students. Determination of the sample was carried out using the purposive sampling technique, the experimental class was XI MIPA 3 as many as 20 students and the control class was XI MIPA 4 as many as 20 students. Using prerequisite test and independent sample t-test. The results showed that the tcount was 8.766 and the ttable was 1.686, at a significant level of 5% (α = 0.05). The test results obtained show that tcount > ttable (8.766 > 1.686), thus Ho is rejected and H1 is accepted. So, it can be concluded that there is an effect of active learning on the MIKiR concept on student learning outcomes in the respiratory system material for class XI MIPA SMAN 2 Luwu Timur